Literature Review: Peran Audit Internal Dalam Penguatan Tata Kelola Perusahaan - Luckyanayu, Iftarista Hardianasti; Huda, Ahmad Nurul; Mappadang, Agoestina (Scimadly Publishing, 2025)
This study aims to comprehensively examine the role of internal audit in strengthening corporate governance through a literature review of various recent academic studies and professional practices. In the context of increasingly complex business dynamics, internal audit plays a strategic role in ensuring compliance, transparency, and the effectiveness of corporate internal control systems. The research employs a qualitative approach using a systematic literature review method, which enables the identification, evaluation, and synthesis of findings from relevant scholarly articles published between 2020 and 2025. The results indicate that internal audit has a significant impact on enhancing the quality of corporate governance, supporting managerial decision-making processes, and reinforcing internal oversight functions and regulatory compliance. Practically, this study contributes by providing recommendations to strengthen the role of internal auditors within organizational structures and to develop adaptive strategies for responding to evolving governance challenges. Thus, this research not only enriches the academic literature but also offers practical guidance for companies in implementing more effective, transparent, and sustainable internal audit practices.